Peutz-Jeghers syndrome - Llard, Washington; Valls, Alberto; Cassinelli, Juan F (Cirugía del Uruguay, 2020)
It is a family and hereditary disease that consists of the association of digestive polyps, especially jejunoileal, with cutaneomucosal pigment spots.